Digital marketing strategy focused on social networks as a competitive advantage in Agencia Aduanal Lilliana Irías Carvajal, San José 2022 - Obando Alán, Kembly Dayana, 1998- (2022)
UCR::Docencia::Artes y Letras::Facultad de Letras::Escuela de Lenguas Modernas